RESEPSI MUSLIMAH AL IRSYAD, FATAYAT, DAN NASYIATUL AISYIYAH TERHADAP MAKNA HIJAB DALAM IKLAN SAMPO DI MEDIA TELEVISI - Atiyatul Mawaddah (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2020)
Hijab or jilbab has become familiar in Indonesia. It is certainly influenced by the increasing of understanding of Muslim women in Indonesia related to their obligations to cover their genitals. Muslimah's interest in hijab has been put well by television advertising providers. The use of hijab in advertisements is solely to attract consumers, with the biggest target market being Muslim women in Indonesia. It has an impact on the proliferation of products that choose advertising stars that are closely related to hijab. One of them is shampoo products, such as the Rejoice shampoo advertisement version of Fatin Shidqia Lubis, Clear version of Sivia Azizah, and Wardah version of Dewi Sandra. Therefore, the researcher used Stuart Hall's encoding decoding reception analysis method, where the audience is positioned as an active audience in interpreting the content of media messages to find out what the meaning of the hijab is shown in Rejoice, Clear, and Wardah shampoo advertisements. As a result, the three Muslim women studied, namely Al Irsyad, Fatayat, and Nasyiatul Aisyiyah, all of them had different results. For Al Irsyad, she turns out that his position is in the hegemonic dominant position for Wardah shampoo commercials and in opposition to Rejoice and Clear shampoo advertisements. Meanwhile, Fatayat is in the dominant hegemonic position for the three shampoo advertisements. And for Nasyiatul Aisyiyah, she is in hegemonic dominance for Wardah, negotiating for Rejoice, and opposing Clear.